2012
DOI: 10.1177/0269881112444941
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline benefits negative symptoms in early schizophrenia: a randomised double-blind placebo-controlled clinical trial in patients on standard treatment

Abstract: The onset and early course of schizophrenia is associated with subtle loss of grey matter which may be responsible for the evolution and persistence of symptoms such as apathy, emotional blunting, and social withdrawal. Such 'negative' symptoms are unaffected by current antipsychotic therapies. There is evidence that the antibiotic minocycline has neuroprotective properties. We investigated whether the addition of minocycline to treatment as usual (TAU) for 1 year in early psychosis would reduce negative sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
183
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(198 citation statements)
references
References 42 publications
8
183
0
3
Order By: Relevance
“…Of note, no study to date has focused primary outcomes on the above symptom constructs, although studies in schizophrenia, focusing on negative symptoms, have come the closest in this regard. For example, both a meta-analysis and two recent randomized clinical trials have demonstrated that minocycline (see caveats above) was superior to placebo on the PANSS negative subscale scores and the SANS, particularly the avolition measure (Chaudhry et al, 2012;Ghanizadeh et al, 2014;Oya et al, 2014).…”
Section: Symptom Specificity For Outcome Variablesmentioning
confidence: 99%
“…Of note, no study to date has focused primary outcomes on the above symptom constructs, although studies in schizophrenia, focusing on negative symptoms, have come the closest in this regard. For example, both a meta-analysis and two recent randomized clinical trials have demonstrated that minocycline (see caveats above) was superior to placebo on the PANSS negative subscale scores and the SANS, particularly the avolition measure (Chaudhry et al, 2012;Ghanizadeh et al, 2014;Oya et al, 2014).…”
Section: Symptom Specificity For Outcome Variablesmentioning
confidence: 99%
“…Similarly, a double blind, randomized placebo-controlled study by Levkovitz et al 142 demonstrated that the add-on treatment of minocycline has a beneficial effect on negative symptoms, cognitive functions and general outcomes in early phase patients with schizophrenia. In a recent randomized doubleblind placebo-controlled clinical trial, minocycline benefitted negative symptoms in early schizophrenia 143 . Despite of the above positive reports, a recent update of efficacy of anti-inflammatory agents to improve symptoms in patients with schizophrenia concluded that minocycline showed no significant effect on symptom severity 144 .…”
Section: Minocyclinementioning
confidence: 99%
“…Der in Fallstudien sowie kleinen Gruppenstudien gefundene Effekt einer Verbesserung der Kognition in einzelnen Domänen konnte in grösseren Plazebo-kontrollierten Doppelblindstudien jedoch nicht nachgewiesen werden [82]. Weitere Substanzen mit initial vielversprechenden Befunden sind das tetrazyklische Antibiotikum Monocyclin, der Nikotinrezeptor-Agonist DMXB-A sowie Hemmer des Glycin-Transporters [83,84]. Diese Befunde konnten allerdings bisher nicht repliziert werden.…”
Section: Ergänzende Medikamentöse Strategienunclassified